Workplace Interventions for Cardiovascular Diseases: Protocol of a Systematic Review and Meta-Analysis - Siques-Urzua, C (NLM (Medline), 2022)
Cardiovascular diseases (CVDs) are the number one cause of death globally, impacting on public and private sectors. Current traditional interventions to prevent CVDs are mainly provided in healthcare centres and even when they are effective, they are not enough to reduce the rising prevalence; therefore, additional strategies are needed. Evidence suggests that health interventions in the workplace supply numerous benefits improving cardiovascular risk factor profiles in individuals. Hence, the aim of this systematic review and meta-analysis is to collate the evidence from randomised controlled trials, cluster randomised trials and quasi-experimental studies of workplace interventions to determine their effectiveness in terms of improving cardiovascular risk factors and preventing CVDs. METHODS AND ANALYSIS: EMBASE, PsycINFO, PubMed, the Cochrane Central Register of Controlled Trials, LILACS, Scopus, Web of Science, WHO International Clinical Trials Registry Platform, ClinicalTrials.gov and ProQuest Dissertations & Theses Global will be searched to include articles on workplace interventions in adults for CVDs events, cardiometabolic risk factors or behavioural risk factors. The study selection, data extraction, risk of bias and the assessment of the quality of the body of evidence will be conducted by two reviewers working in parallel and disagreements will be resolved by consensus or consultations with a third reviewer. Data synthesis will be done by meta-analysis using random-effects models when possible, otherwise the vote counting method will be applied. Statistical heterogeneity will be assessed by a χ2 test and I2 statistics. The quality of the body of evidence for each outcome will be assessed by applying the Grading of Recommendations, Assessment, Development and Evaluation approach. ETHICS AND DISSEMINATION: Ethical approval is not required for this systematic review protocol. The results of the systematic review will be published in a peer-reviewed journal and will be publicly available. PROSPERO REGISTRATION NUMBER: CRD42021276161. © Author(s) (or their employer(s)) 2022. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.